Historical Analysis of Rejection and Acceptance of the Values of Parmalim Beliefs - Syaiful Anwar (Andalas International Journal of Socio-Humanities, 2024)
Parmalim is a belief system of the Batak people that predates the arrival of Islam or Christianity. This belief system was once prominent in the resistance against colonialism during the era of Sisingamangaraja XII, known as the Parhudamdam movement. This paper aims to examine how Parmalim, which has cultural ties to the Batak people, was once prominent in its historical reality and well-established by 1920 but faced rejection since independence despite not being critical of its traditions. The method used is the historical method. The collection of sources comes from the colonial and post-colonial periods. Verification is done by testing the validity of these sources. Meanwhile, interpretation is done through discourse analysis to reveal the meaning of various sources. The results show that there are differences in viewing Parmalim; that as followers of a belief system, they are rejected by adherents of Abrahamic religions, but their cultural traditions are recognized as a pure form of Batak culture.